Language and liberation : feminism, philosophy, and language - Hendricks, Christina; Oliver, Kelly, 1958- (SUNY series in contemporary continental philosophy., 1999)
Presenting new scholarship in feminist language theory, this book addresses issues within diverse traditions, bringing together feminist positions, strategies, and styles in an original way. Gathering together authors with different backgrounds and methods, Language and Liberation puts this diverse scholarship into dialogue. The questions and concerns reflected in these essays are presented within the context of their historical background, provided by the editors' comprehensive introduction. These questions include: Is there a distinction between "female" and "male" language? What is the relationship of feminine/feminist identity to language? What is the value of metaphor for feminist theory and practice?